Examining superstitious beliefs in healthcare through an Islamic lens - Ismail, Mohd Helmie; Salmi, Irfan (Medicine & Health Journal, 2025)
Introduction: Although evidence-based medicine has expanded rapidly, certain superstitious beliefs continue to persist among Muslim medical practitioners. These include the perception that wearing red attire influences referral rates, the attribution of chaotic on-call duties to a colleague labelled as a “Jonah,” the avoidance of the term “quiet” during periods of low patient volume, and the association of full moon phases with increased hospital admissions. Such notions, however, are inconsistent with the principles of Islamic belief. The review aimed to evaluate the potential impact of such beliefs on patient care and to contextualise these practices within the Islamic perspective. Methods: A narrative review of the literature on superstition in medicine was undertaken using the search terms “superstitious belief”, “lunar cycles and black cloud” and “medical practice” in PubMed and Google Scholar. In addition, selected Islamic teachings concerning fate (Qadar) and the attribution of events were examined. Results: There are 8 studies were reviewed from 2007 until 2024. All studies show no significant correlation between lunar cycles and patient volumes, nor between the perception of “black cloud” residents and actual workload. Such superstitions persist due to misattributed causality and the desire to control uncertainty. In Islam, attributing misfortune to people or events contradicts Quranic and Prophetic teachings, which affirm that all outcomes are decreed by Allah, requiring gratitude or patience in response. Conclusion: Superstitious beliefs remain common among Muslim healthcare workers but are not supported by scientific evidence. Islam encourages on trusting Allah’s wisdom and expecting good from Him, discourages blaming individuals or omens, and response to all outcomes as opportunities for gratitude or patience. Continuous education addressing both scientific evidence and Islamic principles may help reduce superstition in the workplace.